Bilateral Prophylactic Nipple-Sparing Mastectomy: Analysis of the Risk-Reducing Effect in BRCA1/2 Mutation Carriers - Staněk, Kryštof; Zimovjanova, Martina; Suk, Petr; Jonas, Filip; Zimovjanová, Anna; Molitor, Martin; Mestak, Ondrej (Aesthetic plastic surgery, 2022)
BACKGROUND: Mutations in the BRCA1 or BRCA2 genes increase the lifetime risk of developing breast cancer to 68-72% by the age of 80. One of the modalities to manage the risk is a prophylactic mastectomy. Bilateral nipple-sparing mastectomy specifically offers the most favorable esthetic outcomes but the evidence for its oncological safety remains limited. Thus, we aimed to compare the occurrence of breast cancer between nipple-sparing mastectomy and surveillance groups of BRCA1 or BRCA 2 mutations carriers. MATERIALS AND METHODS: BRCA1 or BRCA2-positive patients undergoing bilateral prophylactic nipple-sparing mastectomy at our department were identified. Only those unaffected by breast cancer were eligible. Each patient was pair-matched with a BRCA1 or BRCA2-positive patient of equal age from the surveillance group. Breast cancer incidence in both groups was recorded and the results were compared. RESULTS: None of 105 patients who underwent NSM between 2009 and 2019 at a single institution with a mean follow-up time of 50 months developed breast cancer over this time period. One patient in this group died of an unrelated cause. Nine patients from 105 in the match-paired surveillance group were diagnosed with breast cancer during a mean follow-up time of 58.3 months, however, none of them died. CONCLUSION: To the best of our knowledge, this is the largest single-center study of risk-reducing bilateral NSM in healthy BRCA1 or BRCA2 mutation carriers. Based on our results and those of other series, we conclude that NSM in its current form appears to be at least equally as safe as other types of mastectomy for preventing breast cancer in BRCA1 or BRCA2 mutation carriers. LEVEL OF EVIDENCE IV: This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266 .
Keywords: ženské pohlaví; protein BRCA2; nádory prsu; mutace; Female; lidé; Mutation; Humans; BRCA1 Protein; subkutánní mastektomie; Nipples; BRCA2 Protein; prsní bradavky; Breast Neoplasms; protein BRCA1; Mastectomy, Subcutaneous